Hacking Group Claims N.S.A. Infiltrated Backbone of Mideast Bank System. - PERLROTH, NICOLE (New York Times, 2017)
The article reports on claims of the hacking group calling itself the Shadow Brokers about leaking sensitive data from the U.S. National Security Agency, as of April 2017, and mentions that according to the group N.S.A. had infiltrated the backbone of the Middle East's banking infrastructure.